Pengaruh Goal Setting dan Self-Efficacy Terhadap Kinerja Karyawan - Teddy Sutrisno; Tutuk Ari Arsanti (Forum Inovasi Bisnis dan Manajemen, 2023)
This paper aims to gain an understanding of the influence of goal setting and self-efficacy on employee performance. Specifically, this research wants to examine the impact of sales targets and employee self-efficacy on employee’s sales performance. This research was conducted on profit-oriented companies, in particular, employees of the marketing department or sales people who were required to achieve sales targets as part of employee performance appraisals. Quantitative methods were used in this research. The research strategy uses a survey with multiple regression analysis. The results of this study show that goal setting and self-efficacy do not influence an employee's sales performance. Through this empirical study, we not only discover the insignificant influence of goal setting and self-efficacy on employee’s sales performance, but this result also gives explanation about why goal setting and self-efficacy are unable to explain employee’s performance in a certain context. The results of this empirical research provide new insights on how goal setting and self-efficacy works to achieve high performance.